Performance Analysis of AODV Routing Protocol in MANET Using NS2 Simulator - Elwalda, Wisam (Sharwes Scientific Journal, 2025)
Mobile Ad-Hoc Networks (MANETs) are a group of wireless mobile nodes (or routers) that dynamically form an ad hoc network without the use of any existing network infrastructure or central management.This type of network depends on the protocols used and their effectiveness in providing network security. Providing security for these networks is a major challenge. Therefore, this paper examines the protocols used in these networks, attempts to understand their operation, and then determines the appropriate protocol when designing a network of this type.The NS2 simulator was used to simulate the AODV protocol to clearly understand its operation and how data travels across the nodes that comprise the network. This paper aims to simulate the performance of the AODV protocol using the NS2 simulator, while analyzing key performance indicators such as packet delivery ratio (PDR), mean latency, and throughput. The study reviews the setup of the simulation environment, the mechanism for collecting and analyzing data using AWK and Xgraph tools, and visually presents the results through graphs that illustrate the behavior of the protocol in various scenarios.